International patterns of the public awareness of aphasia. Issue 3 (27th November 2015) - Code, Chris; Papathanasiou, Ilias; Rubio‐Bruno, Silvia; de la Paz Cabana, María; Villanueva, Maria Marta; Haaland‐Johansen, Line; Prizl‐Jakovac, Tatjana; Leko, Ana; Zemva, Nada; Patterson, Ruth; Berry, Richard; Rochon, Elizabeth; et al.
Abstract: Background : It has been suggested that public awareness of aphasia is vital for extending services, research support, social inclusion and targeted raising of awareness. Earlier studies show that knowledge of aphasia varies across a range of variables, but is very low compared with other conditions. Aims : To report a series of surveys of public awareness of aphasia from six countries, the largest study conducted this far. Methods & Procedures : Surveys were conducted in Argentina ( N = 800), Canada ( N = 831), Croatia ( N = 400), Greece ( N = 800), Norway ( N = 251) and Slovenia ( N = 400) using the same methodology requesting information on age, sex and occupation, asking whether respondents had heard of aphasia and where they had heard of it. Respondents were tested on their levels of knowledge of aphasia. Outcomes & Results : Results revealed low levels of awareness of aphasia in countries surveyed with marked variability that appeared to interact with occupation, country, age and sex. We surveyed 3483 respondents (mean age = 43.16; SD = 17.68). Between 60% (Croatia) and 16% (Slovenia) said they had heard of aphasia (37.1% overall), but those with actual knowledge ranged from 13.9% (Norway) to 1.0% (Argentina). The combined mean of those with basic knowledge was 9.2%. Those who had heard of aphasia were younger; and females had higher levels of awareness. We also found associations between socio‐economic status and awareness. Those working in health, social and educational spheres had the highest levels. Respondents mainly heard about aphasia through the media and work or personal contact with aphasia. Conclusions & Implications : Levels of awareness are low everywhere in absolute terms, and relative to the awareness of other conditions, with significant variability between countries, sex and socio‐economic status. We examine how surveys can be utilized to plan ways to increase understanding and discuss the comparison of awareness of aphasia with other conditions.